Design and implementation of optical wireless communications with optically powered smart dust motes - O'Brien, D.; Liu, Jingjing; Faulkner, G.; Sivathasan, S.; Yuan, W.; Member, S.; Elston, S. (Institute of Electrical and Electronic Engineers, 2009)
Complete electronic and micro-mechanical systems can now be fabricated on the scale of hundreds of microns. Implementing radio frequency wireless communications with such 'smart dust' is challenging, due to the power required and the small size of any antennas that can be implemented. Optical wireless communications, using a modulated retro-reflector at the smart dust has the advantages of low-power consumption and highly directive channels that allow long communications ranges. In this paper we report the design and implementation of a communications system that uses a base station to communicate with, and power, smart dust motes, over ranges of 10s of metres. A base station that uses holographic beamsteering is described, and dust motes that use silicon ICs to provide communications, power and modulation control. Results indicate the dust mote will operate at a range of over 30m from the base station. © 2009 IEEE.